PELATIHAN PEMASARAN ONLINE BAGI USAHA HOME INDUSTRY MINIATUR MOBIL TRUK PEKON TAMBAHREJO - Muhammad Islam Mahdi (Jurnal PkM Pemberdayaan Masyarakat, 2021)
Digital-based sales technology or as we often know electronic commerce has experienced a very rapid increase as is felt at this time. With very tight trade competition, Miniature Truck Car Industry collaborates with the Higher Education Institute STMIK Pringsewu, to provide training services for home industry business owners to have a digital-based sales platform with the concept of mobile commerce. This Community Service activity aims to provide an understanding of how to market digital-based food products. From this activity, members who have a home industry business can market their products quickly, precisely and safely so that customers can provide convenience to customers.